2021
DOI: 10.7759/cureus.14761
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Variants, Characteristics, and Outcomes Among COVID-19 Patients: A Case Series Analysis at a Tertiary Care Hospital in Karachi, Pakistan

Abstract: IntroductionCoronavirus disease 2019 has become a global threat to public health. The current study investigates alterations in the biological estimates concerning the severity, recovery, mortality, and assessment of treatment-based outcomes. MethodsA case series of 165 COVID-19 patients admitted to OMI Institute (a tertiary care hospital) was conducted between May and August 2020. The data regarding demographic characteristics, comorbid conditions, radiographic abnormalities, biological estimations, symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…NLR levels were significantly higher in both deceased and not improved groups. High NLR level at the administration of TCZ is, therefore, a significant risk factor for mortality in our population, which is consistent with a meta-analysis conducted by Li et al among 34 studies with COVID-19 patients and was also reported by Ahsan et al that high NLR level was a strong predictor of death among COVID-19 patients [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…NLR levels were significantly higher in both deceased and not improved groups. High NLR level at the administration of TCZ is, therefore, a significant risk factor for mortality in our population, which is consistent with a meta-analysis conducted by Li et al among 34 studies with COVID-19 patients and was also reported by Ahsan et al that high NLR level was a strong predictor of death among COVID-19 patients [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, among the laboratory parameters, oxygen saturation, ferritin, D-dimers, creatinine, PT, and INR were significantly altered, and with that, these estimations greatly varied among recovered and deceased patients (p<0.05). These findings are also supported by similar local studies [22,23].…”
Section: Discussionsupporting
confidence: 89%
“…Among the significant predictors of COVID-19 severity and outcomes were age, hypertension, fatigue, abnormal respiratory rate, oxygen saturation, blood glucose level, ferritin, and HADS. Consistent with this, a local case series from Pakistan identified age, presence of comorbidity, high neutrophil-to-lymphocyte ratio (NLR), LDH, and CRP levels as strong predictors of mortality among COVID-19 patients [22], which is also supported by other international studies [24]. But to the best of our knowledge, none of the studies focused on the psychological determinants as the potential predictors of mortality among COVID-19 patients, specifically in Pakistan.…”
Section: Discussionmentioning
confidence: 61%
“…Over 40 peer-reviewed studies ( Table 1 ) have demonstrated studies on the effectiveness of IVM in SARS-CoV-2 infection ( Alam et al, 2020 ; Khan et al, 2020 ; Kishoria et al, 2020 ; Reaz et al, 2020 ; Abd-Elsalam et al, 2021 ; Ahmed et al, 2021 ; Ahsan et al, 2021 ; Aref et al, 2021 ; Behera et al, 2021 ; Cadegiani et al, 2021 ; Chaccour et al, 2021 ; Chahla et al, 2021 ; Chowdhury et al, 2021 ; Elalfy et al, 2021 ; Faisal et al, 2021 ; Ferreira et al, 2021 ; Hellwig and Maia, 2021 ; Krolewiecki et al, 2021 ; Lima-Morales et al, 2021 ; López-Medina et al, 2021 ; Mohan et al, 2021 ; Morgenstern et al, 2021 ; Mukarram, 2021 ; Okumuş et al, 2021 ; Podder et al, 2021 ; Rajter et al, 2021 ; Ravikirti et al, 2021 ; Rezk et al, 2021 ; Seet et al, 2021 ; Shahbaznejad et al, 2021 ; Shoumann et al, 2021 ; Abbas et al, 2022 ; Ascencio-Montiel et al, 2022 ; Babalola et al, 2022 ; Beltran Gonzalez et al, 2022 ; Buonfrate et al, 2022 ; Hazan et al, 2022a ; Kerr et al, 2022 ; Lim et al, 2022 ; Mayer et al, 2022 ; Mustafa et al, 2022 ; Ozer et al, 2022 ; Reis et al, 2022 ; Shimizu et al, 2022 ; Zubair et al, 2022 ), with over 80% of studies showing positive outcomes with IVM treatment. Overall, IVM has shown 60–85% improvement in outcomes, including mortality, ventilation, recovery, clearance, and hospital/ICU admissions.…”
Section: Introductionmentioning
confidence: 99%